2015
DOI: 10.1051/0004-6361/201425545
|View full text |Cite
|
Sign up to set email alerts
|

The broad-band radio spectrum of LS I +61°303 in outburst

Abstract: Aims. Our aim is to explore the broad-band radio continuum spectrum of LS I +61 • 303 during its outbursts by employing the available set of secondary focus receivers of the Effelsberg 100 m telescope. Methods. The clear periodicity of the system LS I +61 • 303 allowed observations to be scheduled covering the large radio outburst in March-April 2012. We observed LS I +61 • 303 on 14 consecutive days at 2. 6, 4.85, 8.35, 10.45, 14.3, 23, and 32 GHz with a cadence of about 12 h followed by two additional observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
(32 reference statements)
2
20
0
Order By: Relevance
“…Oscillations are also present in the radio spectral index α (Fig. 2 d) corroborating the observed spectral index oscillations by Zimmermann et al (2015, see the bottom panel of their Fig. 1).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Oscillations are also present in the radio spectral index α (Fig. 2 d) corroborating the observed spectral index oscillations by Zimmermann et al (2015, see the bottom panel of their Fig. 1).…”
Section: Resultssupporting
confidence: 84%
“…In simultaneous radio and X-ray observations of GRS 1915+105, Klein-Wolt et al (2002) showed that X-ray dips were associated with radio peaks. Oscillations with time scales of days are known to occur in Cyg X-3 (Zimmermann et al 2015). These longer period QPO are present in both total flux density and radio spectral index ( Fig.…”
Section: Introductionmentioning
confidence: 96%
“…• 303 was already proven in the past (Gregory et al 1979;Massi & Kaufman Bernadó 2009) and was recently measured over the entire cm radio band (up to 9 mm) by Zimmermann et al (2015).…”
Section: Interferometric Images Of Ls I +61mentioning
confidence: 86%
“…• 303 as in other microquasars (Massi & Torricelli-Ciamponi 2014;Zimmermann et al 2015) A92, page 8 of 11 F. Jaron et al: Understanding the periodicities in radio and GeV emission from LS I +61…”
Section: Influence Of the θ Interval On Pmentioning
confidence: 99%
“…it dominates at low frequencies. At 8 GHz the second peak is often a minor peak, hardly traceable; instead, simultaneous observations at 2 GHz show a strong second peak, even larger at some epochs than the first peak (Massi & Kaufman Bernadó 2009;Massi 2014;Zimmermann et al 2015). We included data at 5 GHz to be able to cover the first cycles.…”
mentioning
confidence: 99%